The Importance of Physical Education in Elementary Schools for Child Development: A Literature Review - Anggia, Anggia (PT. Anagata Sembagi Education, 2025)
Physical education has a strategic role in supporting the holistic development of elementary school children, covering physical, cognitive, social, and emotional aspects. This study uses a qualitative approach with a literature study method to analyze the importance of physical education at the elementary school level. Data were obtained from various scientific sources such as journals, academic books, and reports from relevant international organizations. The results of the study indicate that physical education contributes to improving basic motor skills, physical fitness, concentration skills, and character building of children through values ​​such as sportsmanship, cooperation, and responsibility. However, the implementation of physical education still faces various obstacles such as minimal time allocation, limited facilities, and low priority in the curriculum. Therefore, it is necessary to rearrange education policies so that physical education gets an equal position with other subjects. Physical education is not only a means of recreation, but also an important part of the national education process. By strengthening the role of physical education, it is hoped that a generation will be created that is physically healthy, mentally tough, and adaptive to the development of the times.